Costs and benefits of company-based training in Vietnam : chances and limitations of applying the BIBB cost-benefit model - Jansen, Anika [Verfasser]; Horn, Steffen [Verfasser]; Nguyen, Thi Hoang Nguyen [Verfasser] (My University, 2017)
"Many countries aim to involve more companies in the vocational education and training system. Transparency of the actual costs and benefits of com-pany-based training activities helps governmental authorities to steer this process adequately and can be used to convince firms to increase their in-volvement in company-based training. This article illustrates the challenges of implementing a cost and benefit study in Vietnam. It discusses the ap-plication of the BIBB cost-benefit model, the implementation of the survey, and the interpretation of the main results under special consideration of the different contextual conditions." (author's abstract ; BIBB-Doku)
Kosten und Nutzen betrieblicher Praktika in Vietnam
Keywords: S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; S 1.6.1 Praktika; I 2.3.4 Asien; Internationale Zusammenarbeit; Kosten-Nutzen-Analyse; Betriebspraktikum; Vietnam